Stiffness, strength and interwall sliding in aligned and continuous multi-walled carbon nanotube/glass composite microcantilevers - Otieno, G; Koos, A; Dillon, F; Yahya, N; Dancer, C; Hughes, G; Grobert, N; Todd, R (Elsevier, 2015)
Individual perfect multi-wall carbon nanotubes (MWCNT) can exhibit exceptional properties, such as an elastic modulus of ∼1 TPa. However, integration of carbon nanotubes (CNTs) in bulk ceramic composites has not yet resulted in the significant improvements in mechanical properties that such data suggest to be achievable. Composites with aligned and continuous CNTs and with high CNT volume fractions might be expected to maximise the improvements. We have produced aligned MWCNT preforms by chemical vapour deposition and fabricated dense, aligned and continuous 20% MWCNT/glass composites. This was achieved by infiltration of a ceramic precursor sol into the interstices of a MWCNT preform and consolidation by hot-pressing. The elastic modulus was measured using microcantilever tests and showed a 32% improvement over that of glass. The Young's modulus inferred for the MWCNTs in the composite was 200 ± 20 GPa. The load-displacement curves showed a non-linear and hysteretic behaviour which was attributed to interwall sliding within the MWCNTs. Apparent bridging of the cracks by the MWCNTs and a load maximum preceding failure were observed in the composite, indicating progressive toughening with crack growth. The results are discussed in terms of the microstructures of the MWCNTs and composites.